The Gastric Section - Exclusion in Gastroduodenal Neoplasic Obstruction - Estefan, Alberto; Pomi, Jorge; Delbene, Roberto; Gateño, Nisso; Praderi, Raúl (Cirugía del Uruguay, 1981)
The procedure of gastric section - exclusion as a palliative treatment of gastroduodenal neoplasic obstruction is analized in its technical and physiopathologic basis.